Development of Analytical Profile of Lamotrigine and its API Formulation - VISHAL CHAUDHARY; SAXENA, VASUNDHARA (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objective: The objective of this review is to put a light on the development of lamotrigine and its active pharmaceutical ingredients formulation with proper demonstration. Method: In the present work, one of the most imperative spectrophotometric method which is RP-HPLC method has been developed for the quantitative estimation of lamotrigine in bulk and pharmaceutical formulations. UV spectrophotometric method which involves the determination of Lamotrigine in bulk and in bulk drug and pharmaceutical formulation has maximum absorption at 307.5nm in methanol. It obeys Beer’s and Lambert’s law in the concentration range of 5-45 µg/ml. A rapid and sensitive RP- HPLC Method with UV detection (270 nm) for routine analysis of Lamotrigine formulation was developed. Chromatography was performed with mobile phase containing a mixture of methanol and Phosphate buffer (65:35v/v) with flow rate 1.0 ml/min. In the range of 20-100 µg/ml, the linearity of lamotrigine shows a correlation co-efficient of 0.9998. The proposed method was validated by determining sensitivity and system suitability parameters.